MOTIVATION AND PARTICIPATION OF FARMERS IN THE AUTP PROGRAM IN SUNGAI PINYUH DISTRICT, MEMPAWAH REGENCY - Sahbudin, Sahbudin; Kurniati, Dewi; Suyatno, Adi (Jurnal AGRISEP, 2022)
The formulation of the problem in this study is the lower the number of AUTP participants in Sungai Pinyuh District, so the purpose of this study is to analyze the level of motivation, the level of participation and the relationship between motivation and participation. This study uses the Likerta scale method (descriptive) then the range spermant test to find a relationship. The research location was chosen by purposive sampling, this means that the Sungai Pinyuh sub-district is an active AUTP participant in Mempawah Regency. Determination of the number of respondents as many as 81 respondents. The results in this study are the level of motivation with a high category, the level of participation is included in the high category, the relationship between motivation and participation has a positive relationship, suggestions in research participants should be involved in the evaluation stage in order to contribute to providing criticism and suggestions